Social Work and the Acute Psychosocial Care of Families in Pediatric Resuscitation Settings: A Single-Site Clinical-Data Mining Study. Issue 6 (2nd November 2022) - Manguy, Alys-Marie; Joubert, Lynette; Gordon, Rob; Oakley, Ed
ABSTRACT: Purpose: Family attendance in pediatric resuscitation situations is currently accepted practice within modern emergency departments. The support of these families has become a key area of practice for emergency department social workers. However, there is limited evidence to guide acute psychosocial care of families who find themselves in these situations. Method: This practice-based research project used a clinical data-mining methodology. Descriptive and inferential analyses of the demographic characteristics and documented psychosocial care needs of 1123 families whose child were cared for in a major pediatric hospital resuscitation area was undertaken, with particular focus on available social work referral and intervention data. Results: Results included family demographic, psychosocial care need and the social work role information. We identify factors impacting on family care needs, social work intervention and service pathways for this population. Conclusion: A skill set for social work clinicians working in pediatric emergency resuscitation settings is proposed.